Skull-base fractures: Pearls of etiopathology, approaches, management, and outcome - K V. L Narasinga Rao; Padilla-Zambrano Huber Said; Luis Rafael Moscote-Salazar; Guru Duatta Satyarthee; V Anil Kumar; Ranabir Pal; Amit Agrawal (Apollo Medicine)
Fractures involving skull bases usually results from high-velocity impacts, i.e., motor vehicular accidents. The estimated incidence of skull-base fracture varies from 4% of all head injuries to 7%–16% of closed head injuries. Many studies have emphasized the importance of the management of basal skull fractures as it can be associated with major neurological deficits, can carry a risk of being missed during clinical evaluation in a busy emergency room and can additionally lead to life-threatening complications including cerebrospinal fluid (CSF) leak and meningitis. In addition to the bony injuries, skull-base fractures can be accompanied by injury to cranial nerves, intracranial blood vessels, and CSF rhinorrhea or otorrhea (particularly fractures involving anterior and middle cranial fossa). In the presence of characteristics clinical features, patient should be thoroughly clinical examination and pertinent investigation with appropriate imaging modality for the presence of additional intracranial lesions and as delayed diagnosis can lead to increase in neurological morbidity and also rarely mortality.